2017
DOI: 10.5897/ajpp2017.4811
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical screening and toxicity profiles of crude extracts of Cissus quadrangularis L. and Solunum incanum L. in mice

Abstract: However, the sub-acute toxicity study exhibited that crude extract of fruit of S. incanum(400 mg/kg) showed relatively higher toxic effects of causing a more pronounced (p<0.05) mortality, body weight loss, and reduction in PCV and Hb levels, compared to negative control. Extracts of C. quadrangularis revealed low mortality and a marginal increase of the hematological parameters. A detailed experimental analysis of these herbs extensively used by the agro-pastoralists of the area is essential to establish thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…Acute toxicity in rodents was performed earlier at the maximum dose, that is, 2000 mg/kg. [16] Extracts caused no visible signs of acute toxicity at the maximum dose, hence, were not performed. [16] Studies have shown that exposure to rotenone altered behavioral and motor deficits, which are similar to human PD, counting muscular rigidity (catalepsy), postural instability, bradykinesia, and unsteady gait.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Acute toxicity in rodents was performed earlier at the maximum dose, that is, 2000 mg/kg. [16] Extracts caused no visible signs of acute toxicity at the maximum dose, hence, were not performed. [16] Studies have shown that exposure to rotenone altered behavioral and motor deficits, which are similar to human PD, counting muscular rigidity (catalepsy), postural instability, bradykinesia, and unsteady gait.…”
Section: Discussionmentioning
confidence: 99%
“…[16] Extracts caused no visible signs of acute toxicity at the maximum dose, hence, were not performed. [16] Studies have shown that exposure to rotenone altered behavioral and motor deficits, which are similar to human PD, counting muscular rigidity (catalepsy), postural instability, bradykinesia, and unsteady gait. [23] A decrease in movement, catalepsy was observed when zebrafish was exposed to rotenone at a dose of 3 pg/mL.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations